Amphoteric straw adsorbent and its preparation method and application

By modified by crushing, alkaline washing and free radicals of straw, preparation of bisexual straw adsorption agents, solving the problem of Eruste and Norfloxacin in the existing technologies, realizing the adsorption The improvement of performance and thermal stability has expanded the scope of application and simplified the process.

CN118558304BActive Publication Date: 2025-01-24WUHAN TEXTILE UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202410838015.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-26
Publication Date
2025-01-24
Estimated Expiration
2044-06-26

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove enrofloxacin and norfloxacin from water, and the preparation process of existing adsorbents is complex and costly, and the application range is limited.

Method used

By modified by crushing, alkaline washing and free radicals, a bisexual straw adsorption agent is prepared. The adsorbent contains cationicaminels and anionic sulfonate, which is used to adsorb Ennohaxing and Norfloxacin.

Benefits of technology

The performance of the straw adsorbent has been significantly improved, with better adsorption performance and thermal stability, and the application scope of straw as an adsorbent has been expanded. The process is simple and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118558304B_ABST
    Figure CN118558304B_ABST
Patent Text Reader

Abstract

The invention discloses a kind of amphoteric straw adsorbent and its preparation method and application, and the preparation method comprises: S1, washing and drying the straw, crushing and sieving, and obtaining straw powder; S2, adding the straw powder into a sodium hydroxide solution, and then heating and stirring; after the treatment is completed, filtering, washing, and drying are carried out to obtain pre-treated straw powder; S3, adding the pre-treated straw powder into a reaction vessel, then adding an initiator and deionized water, and carrying out a pre-reaction under the condition of continuous nitrogen gas; then, dissolving 2-acrylamide-2-methyl-1-propane sulfonic acid and N,N'-methylenebisacrylamide in deionized water and adding them into the reaction vessel, and continuing the reaction; washing and drying are carried out to obtain an amphoteric straw adsorbent. The present invention is based on free radical graft polymerization, and an amphoteric straw adsorbent is prepared, which has a good adsorption effect on ENR and NOR, can simultaneously give play to the advantages of straw materials and adsorption methods, and fully expands the application scope of the straw adsorbent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorbent preparation, and in particular relates to an amphoteric straw adsorbent and a preparation method and application thereof. Background Art

[0002] Straw is a byproduct of agricultural production activities and an important renewable resource. Traditional disposal and utilization methods (such as incineration and returning to the field) have "three difficulties" (difficulty in transformation, difficulty in resale, and difficulty in supervision), and are not conducive to environmental protection and resource conservation. It is still necessary to actively explore new ways to utilize crop straw resources, promote green and sustainable development, and help achieve the "dual carbon" goals.

[0003] The main components of straw are polymers such as cellulose, hemicellulose and lignin, showing typical microtubular fibers of plants. The components are bonded by covalent and non-covalent bonds of functional groups to form a dense three-dimensional structure, which gives straw excellent mechanical properties and stability. Straw has natural structural advantages and surface activity. In addition, it has a wide source, large quantity and low price, and has excellent characteristics and potential as an adsorbent. There are many reports on the research and application of straw adsorbents. The most ideal way to use straw is to simply wash, grind and dry it and then use it directly for pollutant adsorption. However, the surface of straw has a natural wax layer, and there are a large number of hydrogen bonds inside that make the structure tightly bound, resulting in a reduction in the effective adsorption area and adsorption sites. Therefore, it is necessary to design and modify the straw material according to the nature of the pollutant to improve the adsorption performance.

[0004] Commonly used straw modification methods include physical method, chemical method, physicochemical method and biological method, among which chemical method can regulate the surface properties of straw from the microscopic level, and thus is favored. In order to make full use of the inherent advantages of straw raw materials, the modification process should be as simple as possible, with less chemical reagents, low cost, strong pertinence and good effect. Although many methods reported can improve the adsorption performance of straw to a certain extent, there are problems such as large amount of organic reagents and complicated steps in the preparation process. Moreover, the treatment objects are mostly concentrated in heavy metals (such as patent documents CN104368316B, CN105879838A, etc.) and dyes (such as CN107349909B, CN107362780B, CN112169774A, etc.), and the scope of application is limited. Today's water environment problems are becoming increasingly complex, and various emerging pollutants are emerging one after another. It is of great significance to use simple and environmentally friendly methods to carry out targeted design of straw according to the properties of the pollutants, so as to achieve significant performance improvements without destroying its original structural advantages.

[0005] Enrofloxacin (ENR) and norfloxacin (NOR) belong to typical fluoroquinolone antibiotics. With the change of pH, ENR and NOR can exist in the form of anion, zwitterion or cation. Due to the good antibacterial effect of these two antibiotics, they have been widely used in recent years, which also leads to the continuous accumulation of the two in water, and the residual amount increases. The biological method commonly used by major sewage treatment plants at present cannot completely remove it, and the use of adsorption method to remove such difficult-to-degrade pollutants has the advantages of simplicity, high efficiency and low cost. In the prior art, as patent document CN106475066B provides a magnetic powder activated carbon adsorbent, which can be used for the adsorption of organic pollutants (such as tetracycline hydrochloride, oxytetracycline hydrochloride, chloramphenicol hydrochloride, enrofloxacin, ciprofloxacin, lomefloxacin), etc., and is adsorbed by preparing chitosan-Fe magnetic powder; Patent document CN114933344B provides a bifunctional acidic ion exchange adsorbent to remove the application of fluoroquinolone antibiotics in wastewater, which is adsorbed by preparing a bifunctional exchange adsorption resin. The above patent achieves the adsorption of ENR and NOR by preparing a specific adsorbent. How to achieve the adsorption of ENR and NOR based on the utilization of straw has great research significance.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an amphoteric straw adsorbent and a preparation method and application thereof. After being modified by a chemical method, it is applied to the treatment of ENR and NOR, which can simultaneously give play to the advantages of straw materials and adsorption methods and fully expand the application scope of the straw adsorbent.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] In a first aspect, the present invention provides a method for preparing an amphoteric straw adsorbent, comprising the following steps:

[0010] S1. Pretreatment of straw: Pretreatment of straw: Wash and dry the straw, then crush and sieve to obtain straw powder; the straw can be selected from common types, such as sesame, peanut, soybean, etc.; in the above treatment process, crushing and sieving are for the convenience of subsequent use;

[0011] S2, alkali washing of straw: adding the straw powder obtained in step S1 to a sodium hydroxide solution, followed by heating and stirring; after the treatment, filtering, washing and drying are performed to obtain pretreated straw powder; during the above treatment, the wax layer on the surface of the straw can be removed, and the crystallinity of the lignocellulose can be reduced, exposing the active hydroxyl groups, which is beneficial to the next step of treatment;

[0012] S3, graft copolymerization of straw: adding the pretreated straw powder obtained in step S2 into a reaction container, then adding an initiator and deionized water, and conducting a pre-reaction under the condition of continuous nitrogen flow; then, dissolving 2-acrylamide-2-methyl-1-propane sulfonic acid and N,N'-methylenebisacrylamide in deionized water and adding them into the reaction container, and continuing the reaction; after the reaction is completed, washing and drying are performed to obtain an amphoteric straw adsorbent.

[0013] In the above technical scheme, an amphoteric straw adsorbent is prepared by crushing and screening the straw, alkali washing and free radical graft copolymerization, and selecting 2-acrylamide-2-methyl-1-propane sulfonic acid containing both cationic amide groups and anionic sulfonic acid groups as a monomer.

[0014] As a preferred embodiment of the above technical solution, in step S1, the drying temperature is 60-90°C. It is understandable that the above drying temperature can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C or any specific value within the range of 60-90°C, which can be flexibly adjusted by those skilled in the art.

[0015] As a preferred embodiment of the above technical solution, in step S1, the crushing and sieving mesh number is 60 to 200 meshes. It can be understood that the above sieving mesh number can be a value among 60 mesh, 70 mesh, 80 mesh, 90 mesh, 100 mesh, 110 mesh, 120 mesh, 130 mesh, 140 mesh, 150 mesh, 160 mesh, 170 mesh, 180 mesh, 190 mesh, 200 mesh, or any specific value within the range of 60 to 200 meshes, and those skilled in the art can flexibly adjust it.

[0016] As a preferred embodiment of the above technical solution, in step S2, the concentration of the sodium hydroxide solution is 0.5-5 mol / L, and the ratio of straw powder to the sodium hydroxide solution is 1 g: 20-60 mL. It can be understood that the concentration of the sodium hydroxide solution can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2 mol / L, 2.1 mol / L, 2.2 mol / L, 2 .3mol / L, 2.4mol / L, 2.5mol / L, 2.6mol / L, 2.7mol / L, 2.8mol / L, 2.9mol / L, 3mol / L, 3.1mol / L, 3.2mol / L, 3. 3mol / L, 3.4mol / L, 3.5mol / L, 3.6mol / L, 3.7mol / L, 3.8mol / L, 3.9mol / L, 4mol / L, 4.1mol / L, 4.2mol / L, 4.3 mol / L, 4.4mol / L, 4.5mol / L, 4.6mol / L, 4.7mol / L, 4.8mol / L, 4.9mol / L, 5mol / L or any specific value in the range of 0.5-5mol / L; similarly, taking the dosage of straw powder as 1g as an example, the dosage of sodium hydroxide solution can be 20mL, 21mL, 22mL, 23mL, 24mL, 25mL, 26mL, 27mL, 28mL, 29mL, 30mL 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75

[0017] As a preferred embodiment of the above technical solution, in step S2, the heating and stirring treatment temperature is 50-80°C, and the treatment time is 1-5h. It is understandable that the above treatment temperature can be a value among 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or any value within the above range; similarly, the treatment time can be a value among 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, or any value within the above range.

[0018] As a preferred embodiment of the above technical solution, in step S3, the initiator is one of ammonium persulfate, sodium persulfate, and potassium persulfate, preferably ammonium persulfate; the mass ratio of pretreated straw powder, initiator, 2-acrylamide-2-methyl-1-propane sulfonic acid, and N,N'-methylenebisacrylamide is 1:0.1~1:0.5~2:0.1~0.5.

[0019] As the preferred embodiment of the above technical solution, in step S3, the pre-reaction temperature is 60-80°C, and the pre-reaction time is 10-60min. It is understandable that the pre-reaction temperature can be a certain value among 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C or any value within the above range; the pre-reaction time can be a certain value among 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min, 60min or any value within the above range.

[0020] As the preferred embodiment of the above technical solution, in step S3, the reaction temperature (i.e., graft polymerization reaction) is 60-90°C, and the reaction time is 1-4h. It is understandable that the reaction temperature can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C or any value within the above range; the reaction time can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h or any value within the above range.

[0021] In a second aspect, the present invention provides an amphoteric straw adsorbent prepared by the above method.

[0022] In a third aspect, the present invention provides an application of the above-mentioned amphoteric straw adsorbent in adsorbing enrofloxacin and / or norfloxacin. The specific application can be: adding the amphoteric straw adsorbent to wastewater containing ENR and / or NOR, the amount of the adsorbent is 20-50 mg, the concentration of ENR or NOR is 2-40 mg / L, and the adsorption is carried out at pH = 2-10 and the temperature is 25-45°C for a period of time, and then filtering. Obviously, the amount of the adsorbent and the concentration of ENR or NOR can be flexibly adjusted.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The preparation method of the amphoteric straw adsorbent provided by the present invention selects 2-acrylamide-2-methyl-1-propane sulfonic acid containing both cationic amide groups and anionic sulfonic acid groups as a monomer, and prepares the adsorbent based on steps such as alkali washing and free radical graft copolymerization; the preparation process is simple and rapid, the amount of organic solvent used is small, it is non-hazardous and non-polluting, the reaction conditions are mild, and the operation is convenient.

[0025] (2) The present invention focuses on the removal of ENR and / or NOR by selecting appropriate monomers and reaction systems for graft copolymerization modification. The method is flexible and the process is controllable. The relevant ideas can guide the design and preparation of other biomass materials.

[0026] (3) The amphoteric straw adsorbent prepared by the present invention has significantly better adsorption performance and thermal stability for ENR and NOR than the original straw, which expands the application range of straw as an adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The SEM images of the straws of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention are shown; wherein (a) is the amphoteric straw adsorbent of Example 1, (b) is the original straw of Comparative Example 1, and (c) is the alkali-washed straw of Comparative Example 2.

[0028] Figure 2 The energy spectrum scanning results of the straw of Example 1, Comparative Example 1 and Comparative Example 2 are shown; wherein (a) is the amphoteric straw adsorbent of Example 1, (b) is the original straw of Comparative Example 1, and (c) is the alkali-washed straw of Comparative Example 2.

[0029] Figure 3 The thermogravimetric analysis results of the straws of Example 1, Comparative Example 1 and Comparative Example 2 are shown. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In the present invention, the straw used is sesame straw; of course, other common straws such as corn, peanuts, soybeans, cotton, etc. also fall within the scope of protection that the present invention hopes to protect, and the above-mentioned specific usage scenarios do not constitute a specific limitation on the type of straw of the present invention.

[0032] Example 1

[0033] A method for preparing an amphoteric straw adsorbent comprises the following steps:

[0034] S1. Pretreatment of straw: wash the straw with deionized water to remove sand and dust on the surface; then dry the straw at 60°C, crush it with a crusher and pass it through a 100-mesh sieve;

[0035] S2, alkali washing of straw: add 5g of straw powder from step S1 to 200mL of 1mol / L NaOH solution, heat in a water bath at 60°C with stirring for 2h, filter with suction, then add deionized water to immerse the straw, stir for 1h and filter with suction, repeatedly wash with water until the pH of the filtrate is neutral, and dry the straw in an oven at 60°C for later use;

[0036] S3, graft copolymerization of straw: weigh 1g of the pretreated straw powder obtained in step S2 and place it in a three-necked flask; dissolve 0.5g of ammonium persulfate in 80mL of deionized water, then transfer it to a three-necked flask, continue to introduce nitrogen gas and pre-react it in a water bath at 70°C for 20min; then mix 1g of 2-acrylamide-2-methyl-1-propane sulfonic acid and 0.4g of N,N'-methylenebisacrylamide with 20mL of pure water and pour them into a three-necked flask, and carry out graft copolymerization reaction at 70°C for 2h in a nitrogen atmosphere; after the reaction is completed, wash it repeatedly with ethanol and deionized water alternately to remove the unreacted products, and dry the material at 60°C to obtain the amphoteric straw adsorbent.

[0037] The relevant characterization results of the amphoteric straw adsorbent prepared in this example are shown in Figure 1 , Figure 2 , Figure 3 shown.

[0038] from Figure 1It can be seen that the surface of the straw raw material is smooth. After alkali washing, the surface becomes rough and shows a texture structure, indicating that the surface wax layer is removed to a certain extent. The overall morphology of the straw adsorbent is similar to that of the straw after alkali washing, but the surface roughness increases. This is because the monomer has successfully undergone a graft polymerization reaction on the surface.

[0039] from Figure 2 It can be seen that the content of N and S in the amphoteric straw adsorbent is significantly increased compared with the straw raw material and the straw after alkali washing, indicating that 2-acrylamide-2-methyl-1-propane sulfonic acid and N,N'-methylenebisacrylamide are successfully grafted on the straw surface.

[0040] from Figure 3 It can be seen that compared with the straw raw material and the straw after alkali washing, the straw adsorbent has a lower pyrolysis starting temperature, but a higher residual amount, and exhibits better thermal stability overall.

[0041] Example 2

[0042] A method for preparing an amphoteric straw adsorbent comprises the following steps:

[0043] S1. Pretreatment of straw: wash the straw with deionized water to remove sand and dust on the surface; then dry it at 70°C, crush it with a crusher and pass it through an 80-mesh sieve;

[0044] S2, alkali washing of straw: add 5g of straw powder from step S1 to 100mL of 3mol / L NaOH solution, heat in a water bath at 60°C with stirring for 2h, filter with suction, then add deionized water to immerse the straw, stir for 1h, filter with suction, repeatedly wash with water until the pH of the filtrate is neutral, and dry the straw in an oven at 60°C for later use;

[0045] S3, graft copolymerization of straw: weigh 1g of the pretreated straw powder obtained in step S2 and place it in a three-necked flask; dissolve 0.2g of ammonium persulfate in 80mL of deionized water, then transfer it to a three-necked flask, continue to introduce nitrogen gas and pre-react in a water bath at 70°C for 20min; then mix 0.5g of 2-acrylamide-2-methyl-1-propanesulfonic acid and 0.2g of N,N'-methylenebisacrylamide with 20mL of pure water and pour them into a three-necked flask, and carry out graft copolymerization reaction at 60°C for 4h in a nitrogen atmosphere; after the reaction is completed, wash it repeatedly with ethanol and deionized water alternately to remove the unreacted products, and dry the material at 60°C to obtain the amphoteric straw adsorbent.

[0046] Example 3

[0047] A method for preparing an amphoteric straw adsorbent comprises the following steps:

[0048] S1. Pretreatment of straw: wash the straw with deionized water to remove sand and dust on the surface; then dry the straw at 90°C, crush it with a crusher and pass it through an 80-mesh sieve;

[0049] S2, alkali washing of straw: add 5g of straw powder from step S1 to 300mL of 5mol / L NaOH solution, heat in a water bath at 80°C with stirring for 1h, filter with suction, then add deionized water to immerse the straw, stir for 1h, filter with suction, repeatedly wash with water until the pH of the filtrate is neutral, and dry the straw in a 60°C oven for later use;

[0050] S3, graft copolymerization of straw: weigh 1g of the pretreated straw powder obtained in step S2 and place it in a three-necked flask; dissolve 1g of ammonium persulfate in 80mL of deionized water, then transfer it to a three-necked flask, continue to introduce nitrogen gas and pre-react it in a water bath at 70°C for 20min; then mix 2g of 2-acrylamide-2-methyl-1-propanesulfonic acid and 0.5g of N,N'-methylenebisacrylamide with 20mL of pure water and pour them into a three-necked flask, and carry out graft copolymerization reaction at 90°C for 1h in a nitrogen atmosphere; after the reaction is completed, wash it repeatedly with ethanol and deionized water alternately to remove the unreacted products, and dry the material at 60°C to obtain the amphoteric straw adsorbent.

[0051] Comparative Example 1

[0052] Compared with Example 1, the straw in Comparative Example 1 is only processed in step S1, that is, the straw is washed with deionized water to remove sand and dust on the surface; then dried at 60° C., crushed with a crusher and passed through a 100-mesh sieve.

[0053] Comparative Example 2

[0054] Compared with Example 1, the straw in Comparative Example 1 is only processed in steps S1 and S2, that is, a straw modification method comprises the following steps:

[0055] S1. Pretreatment of straw: wash the straw with deionized water to remove sand and dust on the surface; then dry the straw at 60°C, crush it with a crusher and pass it through a 100-mesh sieve;

[0056] S2. Alkaline washing of straw: add 5 g of straw powder from step S1 to 200 mL of 1 mol / L NaOH solution, heat in a 60°C water bath with stirring for 2 h, filter with suction, then add deionized water to immerse the straw, stir for 1 h, filter with suction, repeatedly wash with water until the pH of the filtrate is neutral, and dry the straw in a 60°C oven for later use.

[0057] Application Example 1

[0058] The removal effect of the prepared amphoteric straw adsorbent under different solution initial pH conditions was investigated. The specific steps are as follows:

[0059] Accurately weigh 50 mg of the amphoteric straw adsorbent prepared in Example 1, add 50 mL of 10 mg / L ENR or NOR solution, adjust the pH values ​​to 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, respectively, and place in a constant temperature air bath oscillator, oscillate at 25 ° C for 24 h, the speed is 150 r / min, determine the concentration of residual ENR or NOR in the solution, and calculate the removal rate. The removal rate is calculated according to the following formula (the same below):

[0060]

[0061] Where, C0 is the concentration of ENR or NOR in the solution before adsorption, mg / L; C e It is the concentration of ENR or NOR remaining in the solution after reaching adsorption equilibrium, mg / L.

[0062] The test results are shown in Table 1.

[0063] Table 1 Effect of initial pH value of solution on the effect of amphoteric straw adsorbent

[0064]

[0065] As shown in Table 1, when the pH value is 7.0, the straw adsorbent has the best effect on ENR, with a removal rate of 92.67%; when the pH value is 6.0, the straw adsorbent has the best effect on NOR, with a removal rate of 92.20%. In the range of pH = 4.0 to 9.0, the straw has a good removal effect on both ENR and NOR, indicating that the amphoteric straw adsorbent prepared by the present invention has a wide pH application range. In particular, the adsorption effect is best when the pH is 7.

[0066] Application Example 2

[0067] To explore the removal effect of amphoteric straw adsorbent at different dosages, the specific steps are as follows:

[0068] Take different amounts of the amphoteric straw adsorbent prepared in Example 1, add 50 mL of 10 mg / L ENR or NOR solution, adjust the pH value of the ENR solution to 7.0, and the pH value of the NOR solution to 6.0, place it in a constant temperature air bath oscillator, oscillate at 25°C for 24 h, and the speed is 150 r / min. Determine the concentration of residual ENR or NOR in the solution and calculate the removal rate. The results are shown in Table 2.

[0069] Table 2 Effect of dosage of amphoteric straw adsorbent on removal effect

[0070]

[0071] It can be seen from Table 2 that when the adsorbent dosage is more than 30 mg, the removal rate of ENR and NOR can reach more than 90%. When the adsorbent dosage is 70 mg, the adsorbent has a removal rate of 96.53% for ENR and 98.12% for NOR.

[0072] Application Example 3

[0073] To explore the removal effect of amphoteric straw adsorbent at different adsorption times, the specific steps are as follows:

[0074] Accurately weigh 50 mg of the amphoteric straw adsorbent prepared in Example 1, add 50 mL of ENR or NOR solution with a concentration of 10 mg / L, adjust the pH value of the ENR solution to 7.0, and the pH value of the NOR solution to 6.0, place it in a constant temperature air bath oscillator, oscillate at 25°C for different times, and the speed is 150 r / min. Determine the concentration of residual ENR or NOR in the solution, and calculate the removal rate. The results are shown in Table 3.

[0075] Table 3 Effect of adsorption time on the effect of amphoteric straw adsorbent

[0076]

[0077] It can be seen from Table 3 that the straw adsorbent can adsorb ENR and NOR quickly and efficiently, and the adsorption equilibrium can be basically reached in 30 minutes.

[0078] Application Example 4

[0079] To explore the adsorption effect of different adsorbents, the specific steps are as follows:

[0080] Accurately weigh 20 mg of the amphoteric straw adsorbent in Example 1, the original straw in Comparative Example 1, and the alkali-washed straw in Comparative Example 2, respectively add 50 mL of 10 mg / L ENR or NOR solution, place in a constant temperature gas bath oscillator, oscillate at 25 ° C for 24 h, the speed is 150 r / min, determine the concentration of residual ENR or NOR in the solution, calculate the removal rate, and the results are shown in Table 4.

[0081] Table 4 Comparison of the effects of three adsorbents

[0082]

[0083] As shown in Table 4, the original straw has a poor effect on ENR and NOR, the alkali-washed straw has a better removal effect than the original straw, and the amphoteric straw has a significantly better removal effect on ENR and NOR than the original straw and the alkali-washed straw, indicating that the preparation method provided by the present invention can effectively improve the performance of the straw adsorbent.

[0084] Obviously, the amphoteric straw adsorbent prepared by the present invention uses straw as raw material, which improves the utilization value of straw; the obtained adsorbent has a very good effect on the adsorption of ENR and NOR and has broad application value.

[0085] The present invention illustrates the technical concept of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of individual raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. Use of an amphoteric straw adsorbent in the adsorption of enrofloxacin and / or norfloxacin, characterized in that: The preparation of the amphoteric straw adsorbent comprises the following steps: S1. Pretreatment of straw: washing and drying the straw, crushing and sieving the straw to obtain straw powder; S2, alkali washing of straw: adding the straw powder obtained in step S1 to a sodium hydroxide solution, followed by heating and stirring; after the treatment, filtering, washing and drying are performed, and the pretreated straw powder is obtained; S3, graft copolymerization of straw: adding the pretreated straw powder obtained in step S2 to a reaction container, then adding an initiator and deionized water, and performing a pre-reaction under the condition of continuous nitrogen flow; then, dissolving 2-acrylamide-2-methyl-1-propane sulfonic acid and N,N'-methylenebisacrylamide in deionized water and adding them to the reaction container, and continuing the reaction; after the reaction is completed, washing and drying are performed to obtain an amphoteric straw adsorbent; Wherein, in step S3, the pre-reaction temperature is 60-80°C, and the pre-reaction time is 10-60 min; Wherein, in step S3, the reaction temperature is continued to be 60-90°C, and the reaction time is 1-4h; Among them, in step S3, the initiator is one of ammonium persulfate, sodium persulfate, and potassium persulfate; the mass ratio of pretreated straw powder, initiator, 2-acrylamide-2-methyl-1-propane sulfonic acid, and N,N'-methylenebisacrylamide is 1:0.1~1:0.5~2:0.1~0.

5.

2. The use according to claim 1, characterized in that: In step S1, the drying temperature is 60-90°C.

3. The use according to claim 1, characterized in that: In step S1, the crushing and sieving mesh size is 60-200 meshes.

4. The use according to claim 1, characterized in that: In step S2, the concentration of the sodium hydroxide solution is 0.5-5 mol / L, and the usage ratio of the straw powder to the sodium hydroxide solution is 1 g: 20-60 mL.

5. The use according to claim 1, characterized in that: In step S2, the heating and stirring treatment temperature is 50-80°C, and the treatment time is 1-5 hours.

Citation Information

Patent Citations

  • A kind of mercapto cellulose straw adsorbent and its preparation method and recovery of precious metal silver

    CN104368316B

  • Method for preparing efficient heavy metal adsorbent from modified cotton stalk biomass charcoal

    CN105879838A

  • Preparation methods, products and applications of magnetic powder activated carbon adsorbents

    CN106475066B

  • A method for preparing a magnetic straw cellulose dye adsorbent

    CN107349909B

  • A method for preparing straw dye adsorbent with a semi-interpenetrating network structure

    CN107362780B